Particle decay of astrophysically-important 19Ne levels. (August 2019) - Bardayan, D W; Chipps, K A; Ahn, S; Blackmon, J C; Greife, U; Jones, K L; Kontos, A; Kozub, R L; Linhardt, L; Manning, B; Matos, M; O'Malley, P D; et al.
Abstract: The 15 O(α, γ) 19 Ne reaction is an important trigger reaction leading to the rapid proton ( rp ) capture process in X-ray bursts. The primary uncertainty in determining its astrophysical rate is the uncertain α branching ratios of levels near Ex = 4.1 MeV in 19 Ne. These states have been populated in a study of the 20 Ne( p, d ) 19 Ne reaction, and α branching ratios are reported in this manuscript.